2019
DOI: 10.26434/chemrxiv.8867651.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast Ring-Opening of an Intermediary α-Stannyl-β-Cyclopropylvinyl Radical Does Not Support Formation of an α-Stannylvinyl Cation in the O-Directed Free Radical Hydrostannation of Dialkyl Acetylenes

Abstract: 2019). Fast ring-opening of an intermediary αstannyl-β-cyclopropylvinyl radical does not support formation of an α-stannylvinyl cation in the O-directed free radical hydrostannation of dialkyl acetylenes. Chemical Communications. https://doi.O-directed hydrostannation of b-cyclopropyl propargyl alcohol 22 with stannanes and cat. Et 3 B in THF/H 2 O or PhMe/MeOH fails to deliver any detectable products of a-stannylvinyl cation capture. Instead only a-stannyl-b-cyclopropylvinyl radical intermediates can be detec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
3
0
Order By: Relevance
“…For example, recent mechanistic studies into "classical" reactions involving tin hydrides have revealed fascinating complexity and paved the way to rational development of improved reaction protocols. [14][15][16][17][18][19] The addition of antimony hydrides (primary or secondary stibines) to multiple bondshydrostibination -has been explored to a very limited extent, 20, 21 with well-defined examples being restricted to cases that proceed under Lewis-acid or radical-initiator (azobisisobutyronitrile, AIBN) mediated conditions. 22,23 As part of our exploration into new structure and reactivity at antimony and bismuth centres, 24,25 we recently reported the first definitive catalyst-and additive-free addition of stibines to alkenes, alkynes, ketones, and azobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent mechanistic studies into "classical" reactions involving tin hydrides have revealed fascinating complexity and paved the way to rational development of improved reaction protocols. [14][15][16][17][18][19] The addition of antimony hydrides (primary or secondary stibines) to multiple bondshydrostibination -has been explored to a very limited extent, 20, 21 with well-defined examples being restricted to cases that proceed under Lewis-acid or radical-initiator (azobisisobutyronitrile, AIBN) mediated conditions. 22,23 As part of our exploration into new structure and reactivity at antimony and bismuth centres, 24,25 we recently reported the first definitive catalyst-and additive-free addition of stibines to alkenes, alkynes, ketones, and azobenzene.…”
Section: Introductionmentioning
confidence: 99%
“… 88 91 Nevertheless, recent publications have started to focus in this transformation for the synthesis of allenes showing carbon-heteroatom bonds, not easily accessible through any other approach. Thus, B-, 92 P-, 93 and Sn-decorated allenols 29 – 31 , 94 96 have been synthesized using different transition metals as catalysts and mild reaction conditions ( Scheme 7 ).…”
Section: Synthesis Of Allenolsmentioning
confidence: 99%
“…For example, recent mechanistic studies into "classical" reactions involving tin hydrides have revealed fascinating complexity and paved the way to rational development of improved reaction protocols. [14][15][16][17][18][19] The addition of antimony hydrides (primary or secondary stibines) to multiple bondshydrostibination -has been explored to a very limited extent, 20,21 with well-defined examples being restricted to cases that proceed under Lewis-acid or radical-initiator (azobisisobutyronitrile, AIBN) mediated conditions. 22,23 As part of our exploration into new structure and reactivity at antimony and bismuth centres, 24,25 we recently reported the first definitive catalyst-and additive-free addition of stibines to alkenes, alkynes, ketones, and azobenzene.…”
Section: Introductionmentioning
confidence: 99%